KETOPRAK DOR: AWAL MULA KEBERADAANNYA DI ACEH TENGAH - Susandro, Susandro; H, Afrizal (Paradigma: Jurnal Kajian Budaya, 2024)
This article discusses the origin of the Ketoprak Dor art in Paya Tumpi Kampong, Kebayakan District, Central Aceh. This form of art is interesting because it demonstrates that change or development of an art does not only arise from the artist’s own creative processes, but it may also occur due to external factors. Thus, a qualitative research approach with descriptive analysis method was used to investigate this cultural phenomenon. This research proves that Ketoprak Dor originated from Deli, North Sumatra. There were two events that prompted its emergence. First, in 1950s, a Ketoprak Dor group from Deli performed in Bies District, Central Aceh. Second, in the same decade, a group of people from Medan migrated to Bies and brought a set of Ketoprak Dor musical instruments and wanted to sell it there. However, the Bies residents could not purchase it, but the Paya Tumpi residents accepted the deal. Thus, they formed a Ketoprak Dor art group named “Langeng Madio Utomo”, which was later changed to “Sanggar Ketoprak Rahayu Cipto Rukun” in the following decade. Even though they had been on hiatus for three decades from 1990s, in the past few years the group has been active again. It can be concluded that external factors can bring about changes in an art’s purposes, form, style, and meaning.